TET2 and TET3 regulate GlcNAcylation and H3K4 methylation through OGT and SET1/COMPASS. (25th January 2013) - Deplus, Rachel; Delatte, Benjamin; Schwinn, Marie K; Defrance, Matthieu; Méndez, Jacqui; Murphy, Nancy; Dawson, Mark A; Volkmar, Michael; Putmans, Pascale; Calonne, Emilie; Shih, Alan H; Levine, Ross L; et al.
<x xml:space="preserve">Abstract</x> TET proteins convert 5‐methylcytosine to 5‐hydroxymethylcytosine, an emerging dynamic epigenetic state of DNA that can influence transcription. Evidence has linked TET1 function to epigenetic repression complexes, yet mechanistic information, especially for the TET2 and TET3 proteins, remains limited. Here, we show a direct interaction of TET2 and TET3 with O‐GlcNAc transferase (OGT). OGT does not appear to influence hmC activity, rather TET2 and TET3 promote OGT activity. TET2/3–OGT co‐localize on chromatin at active promoters enriched for H3K4me3 and reduction of either TET2/3 or OGT activity results in a direct decrease in H3K4me3 and concomitant decreased transcription. Further, we show that Host Cell Factor 1 (HCF1), a component of the H3K4 methyltransferase SET1/COMPASS complex, is a specific GlcNAcylation target of TET2/3–OGT, and modification of HCF1 is important for the integrity of SET1/COMPASS. Additionally, we find both TET proteins and OGT activity promote binding of the SET1/COMPASS H3K4 methyltransferase, SETD1A, to chromatin. Finally, studies in Tet2 knockout mouse bone marrow tissue extend and support the data as decreases are observed of global GlcNAcylation and also of H3K4me3, notably at several key regulators of haematopoiesis. Together, our results unveil a step‐wise model, involving TET–OGT interactions, promotion of GlcNAcylation, and influence on H3K4me3 via SET1/COMPASS, highlighting a novel means by which TETs may induce transcriptional activation.